On the question of ethnic expressiveness of the material culture of the nomads of the Ulug Ulus. - Chentsov, Yaroslav (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
Purpose. To determine how well-founded is the tradition of interpreting certain types of material culture as indicators of the ethnic identity of the nomads of the Ulug Ulus of the mid-thirteenth to fourteenth centuries on the example of a rod without a kink for the Pechenegs and a two-wheeled cart or harp for the Cumans from two burial mounds in the modern territory of the Ukrainian Steppe, namely burial mound 1 of mound 8 near the village of Plavni, Odesa region, and burial mound 3 near the village of Blahodatne, Dnipro region.Methods. The study used general scientific and special historical methods, in particular, historical and comparative, historical and genetic, methods of analysis, synthesis and classification.Scientific novelty. The issue of determining ethnic identity based on archaeological data is quite complex and poorly studied in Ukrainian historiography, especially when it comes to a period or ethnic group for which there are almost no written sources. Therefore, the study of this issue in relation to the nomads of the Ulug Ulus, who themselves have rarely attracted the attention of modern Ukrainian researchers, will help fill in the ‘white spots’ in Ukrainian archaeological science and draw attention to this complex and interesting problem.Conclusions. As a result of the analysis of two selected mound burials of the mid-13th - 14th centuries, the time of the Ulug Ulus' domination of the Ukrainian steppe, two types of material culture were described - a rod without a kink and a two-wheeled cart or arba, which can mark two large ethnic groups of nomads - Pechenegs and Cumans, respectively. Based on the analysis of the socio-historical context of these types of material culture, it can be shown that these two artefacts can in fact be used as markers of the ethnic identity of the mentioned nomadic ethnic groups. At the same time, the question of how stable the nomads' attitude to these types was over time and in what other contexts, besides ethnicity, they can serve as identity markers, remains open and requires expanding the source base for further understanding.